(Im)Possibilities of Latinx School Board Members' Educational Leadership Toward Equity. (April 2019) - Sampson, Carrie
Purpose: The purpose of this article is to examine how and why Latinx school board members address educational equity, both in general and as related to English learners (ELs).Research Method: This study used a qualitative multiple case study design to examine the leadership of six Latinx school board members representing three different school districts in the U.S. Mountain West region. Data included semi-structured interviews and archival materials.Findings: This study emphasizes the counter-stories of these Latinx school board members, pointing to how family, identity, and encounters with inequities often informed their efforts in addressing equity. Findings also illustrate how most of these board members employed strategies of embracing or avoiding representation, coalition-building, and public advocacy or political neutrality toward equity, with limited and inconsistent results for ELs. Finally, these Latinx school board members often experienced backlash from colleagues and voters that coincided with their efforts.Conclusion: These findings signify that Latinx school board members are often among the most committed on school boards to improving educational equity for ELs and other underserved populations. Moreover, their leadership provides unique and significant representation for these communities that lead to interesting possibilities. Yet Latinx school board members experience several internal and external challenges that make it nearly impossible for them to sufficiently expand educational opportunities for the aforementioned populations.